The Relationship Between Physical Activity, Sleep Quality, And Physical Fitness Among Ssb Persisac Athletes - Wiwit Bintang Permatasari; Maftukin Hudah; Bertika Kusuma Prastiwi (DEPARTEMEN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2026)
Physical fitness is a key component of athletic performance, particularly among soccer players who require endurance, recovery, and optimal physical condition. Previous research has reported inconsistent findings regarding the relationship between physical activity, sleep quality, and physical fitness. Some studies have found significant associations, while others have reported non-significant results. Furthermore, evidence focusing on adolescent soccer players in local soccer schools remains limited, particularly in the Indonesian context. Therefore, this study aimed to examine the relationship between physical activity, sleep quality, and physical fitness, as well as changes in these variables over a two-week observation period among athletes at SSB Persisac Semarang. This study employed a quantitative correlational design with pre-test and post-test measurements involving 25 athletes selected through purposive sampling. Physical activity was assessed using the Global Physical Activity Questionnaire (GPAQ), sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI), and physical fitness was evaluated using the Nusantara Student Fitness Test (TKPN). Data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, Spearman’s rank correlation, and the Wilcoxon signed-rank test. Spearman’s correlation was used to determine the relationship between variables, while the Wilcoxon test was used to compare pre-test and post-test measurements. The results showed that physical activity had a weak positive correlation with physical fitness (r = 0.176; p = 0.399), while sleep quality had a weak negative correlation with physical fitness (r = −0.162; p = 0.439), with both relationships being statistically insignificant. The Wilcoxon test revealed significant changes in sleep quality (p = 0.006) and physical fitness (p = 0.001), while physical activity did not undergo a significant change (p = 0.145). These findings suggest that physical activity and sleep quality were not significantly associated with physical fitness among athletes at SSB Persisac Semarang; however, significant changes in sleep quality and physical fitness were observed during the two-week observation period